Guide to construction and use of 130 mm (5.25 in) flexible disk cartridges for data interchange, using modified frequency modulation recording at 13 262 ftprad, on 80 tracks each side. Track format B for 80 tracks Part 3, (30th September 1988) - British Standards Institution,
No abstract available